2022
DOI: 10.1111/den.14240
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic approach in the diagnosis of high‐grade pancreatic intraepithelial neoplasia

Abstract: Early diagnosis of pancreatic ductal adenocarcinoma (PDAC) is essential for improving prognosis; however, diagnosing PDAC at an early stage is challenging. In patients with localized high‐grade pancreatic intraepithelial neoplasia (HG‐PanIN), whose tumorous lesion is undetectable on cross‐sectional images such as computed tomography or magnetic resonance image, long‐term survival is expected. Pancreatic cystic lesions or main pancreatic duct (MPD) dilatation are important indirect findings for the initial diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
(183 reference statements)
0
18
0
Order By: Relevance
“…Recently, some retrospective cohort studies suggested distinctive imaging features that can be used to suspect small PDAC including HG-PanIN, including: focal pancreatic parenchyma atrophy, stenosis of the pancreatic duct and main pancreatic duct dilation. 12,61 Especially for patients without a pancreatic mass, repeated PJC using ENPD is a feasible method that is important for the diagnosis of early-stage PDAC including HG-PanIN. 3,11,12…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…Recently, some retrospective cohort studies suggested distinctive imaging features that can be used to suspect small PDAC including HG-PanIN, including: focal pancreatic parenchyma atrophy, stenosis of the pancreatic duct and main pancreatic duct dilation. 12,61 Especially for patients without a pancreatic mass, repeated PJC using ENPD is a feasible method that is important for the diagnosis of early-stage PDAC including HG-PanIN. 3,11,12…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…Early detection of pancreatic cancer is essential to provide the affected individual with a fair chance of survival beyond five years. However, most imaging techniques, including MRI, fail to identify conclusively subtle changes observed in the pre-malignant stages, such as the pancreatic intraepithelial neoplasia, which is commonly associated with the tumorigenesis of PDAC [ 72 ]. Even an individual with stage I (localized) pancreatic cancer has only a 39% survival rate over a five-year period [ 73 ].…”
Section: Mrimentioning
confidence: 99%
“… 5 , 6 Although carcinoma in situ (CIS) of the pancreas without mass formation occurs, its diagnosis by EUS‐FNA is not possible; instead, conventional diagnostic endoscopic retrograde cholangiopancreatography (ERCP) is required. 7 , 8 The efficacy of serial pancreatic juice aspiration cytological examination (SPACE) via an endoscopic naso‐pancreatic drainage (ENPD) tube has also been reported, 8 but it is sometimes difficult to collect an adequate volume for analysis. The diagnostic performance of ERCP‐based tissue sampling may be inferior to that of EUS‐FNA, 9 and the incidence of post‐ERCP pancreatitis (PEP) cannot be negligible.…”
Section: Introductionmentioning
confidence: 99%